2020
DOI: 10.3174/ajnr.a6570
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Distal Arterial Collapse in Stenting of Atherosclerotic Near-Occlusion of the Carotid Artery

Abstract: BACKGROUND AND PURPOSE: Carotid near-occlusion has been subclassified into near-occlusion with and without collapse. We aimed to compare the technical success and perioperative complication rates of carotid artery stent placement with special attention to these subtypes to see whether there is a clinical relevance of this subclassification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Unlike other carotid artery stenoses, pre-operative intracranial perfusion was especially poor in patients with CNO, so we should attach great importance to the prevention and treatment of CHS. Cay et al ( 26 ) treated 59 CNO patients with CAS, 8.6% of the patients suffered from hyperperfusion syndrome during the periprocedural period. Strict blood pressure control, drugs for preventing brain edema, and oxygen-free radical scavenging drugs could decrease the incidence of CHS ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other carotid artery stenoses, pre-operative intracranial perfusion was especially poor in patients with CNO, so we should attach great importance to the prevention and treatment of CHS. Cay et al ( 26 ) treated 59 CNO patients with CAS, 8.6% of the patients suffered from hyperperfusion syndrome during the periprocedural period. Strict blood pressure control, drugs for preventing brain edema, and oxygen-free radical scavenging drugs could decrease the incidence of CHS ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] In addition, it has been reported that CAS failed due to difficulty in system delivery, causing dissection and spasm. [ 1 , 10 , 12 ] Therefore, device induction into a collapsed ICA should be done with caution. Wingspan does not have good vessel tracking, and the condition of the vessels proximal to the stenosis makes it difficult to guide it to the stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…None of the modern prospective carotid revascularization trials, such as the Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) 8 , 9 and International Carotid Stenting Study (ICSS) 10 , 11 , included CANO patients. Several recent observational studies reported improvement in cerebral hemodynamics and cognitive functions, and reduced risk of stroke after carotid artery stenting (CAS) in CANO patients 12 15 . However, the technical difficulty and risk of periprocedural complications, especially hyperperfusion syndrome, may be underestimated and should be investigated 12 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent observational studies reported improvement in cerebral hemodynamics and cognitive functions, and reduced risk of stroke after carotid artery stenting (CAS) in CANO patients 12 15 . However, the technical difficulty and risk of periprocedural complications, especially hyperperfusion syndrome, may be underestimated and should be investigated 12 , 16 . We hereafter reported our results of CAS in CANO patients.…”
Section: Introductionmentioning
confidence: 99%